Lady in the water : a classic Bedtime stoy for a new generation - Shyamalan, M. Night; Giamatti, Paul; Dallas Howard, Bryce
Apartment building superintendent Cleveland Heep rescues what he thinks is a young woman from the pool he maintains. When he discovers that she is actually a character from a bedtime story who is trying to make the journey back to her home, he works with his tenants to protect his new friend from the creatures that are determined to keep her in our world.